Incremental prognostic value of hybrid [15O]H2O positron emission tomography-computed tomography: combining myocardial blood flow, coronary stenosis severity, and high-risk plaque morphology - Roel S Driessen; Michiel J Bom; Pepijn A van Diemen; Stefan P Schumacher; Remi M Leonora; Henk Everaars; Albert C van Rossum; Pieter G Raijmakers; Peter M van de Ven; Cornelis C van Kuijk; Adriaan A Lammertsma; Juhani Knuuti; et al. (Oxford University Press, 2022)
Aims
This study sought to determine the prognostic value of combined functional testing using positron emission tomography (PET) perfusion imaging and anatomical testing using coronary computed tomography angiography (CCTA)-derived stenosis severity and plaque morphology in patients with suspected coronary artery disease (CAD).
Methods and results
In this retrospective study, 539 patients referred for hybrid [15O]H2O PET-CT imaging because of suspected CAD were investigated. PET was used to determine myocardial blood flow (MBF), whereas CCTA images were evaluated for obstructive stenoses and high-risk plaque (HRP) morphology. Patients were followed up for the occurrence of all-cause death and non-fatal myocardial infarction (MI). During a median follow-up of 6.8 (interquartile range 4.8–7.8) years, 42 (7.8%) patients experienced events, including 23 (4.3%) deaths, and 19 (3.5%) MIs. Annualized event rates for normal vs. abnormal results of PET MBF, CCTA-derived stenosis, and HRP morphology were 0.6 vs. 2.1%, 0.4 vs. 2.1%, and 0.8 vs. 2.8%, respectively (P < 0.001 for all). Cox regression analysis demonstrated prognostic values of PET perfusion imaging [hazard ratio (HR) 3.75 (1.84–7.63), P < 0.001], CCTA-derived stenosis [HR 5.61 (2.36–13.34), P < 0.001], and HRPs [HR 3.37 (1.83–6.18), P < 0.001] for the occurrence of death or MI. However, only stenosis severity [HR 3.01 (1.06–8.54), P = 0.039] and HRPs [HR 1.93 (1.00–3.71), P = 0.049] remained independently associated.
Conclusion
PET-derived MBF, CCTA-derived stenosis severity, and HRP morphology were univariably associated with death and MI, whereas only stenosis severity and HRP morphology provided independent prognostic value.